Azerbaijan Treasures – impresje na temat azerskich instytucji kultury - Golinowska, Karolina (Człowiek i Społeczeństwo, 2017)
The aim of this article is to present Azerbaijan cultural institutions and their program in the socio-political context. The processes of forming modern Azeri identity narrative have a great impact on institutional sphere that refers both to an ancient history and modern life style. The analysis is based on three institutions located in Baku: The Heydar Aliyev Center, Museum of Modern Art Baku and YARAT Contemporary Art Space. Their exhibitionary program reflects cosmopolitan aspirations of political authorities. However, it ceases to become an intellectually challenging experience, reducing interest in art to an activity of enhancing prestige. Karolina Golinowska, Azerbaijan Treasures – impresje na temat azerskich instytucji kultury [Azerbaijan Treasures – impressions on Azerbaijani cultural institutions], edited by W. Bryl-Roman, „Człowiek i Społeczeństwo” vol. XLIII: Projektowanie w latach 70. [Designing in the 1970s], Poznań 2017, pp. 217-224, Adam Mickiewicz University. Faculty of Social Sciences Press. ISSN 0239-3271.